2016
DOI: 10.1002/bdra.23576
|View full text |Cite
|
Sign up to set email alerts
|

Using state and provincial surveillance programs to reduce risk of recurrence of neural tube defects in the United States and Canada: A missed opportunity?

Abstract: Background Once a woman has had a fetus or infant affected with a neural tube defect (NTD), the risk of recurrence is approximately 3%. This risk can be significantly reduced by folic acid supplement consumption during the periconceptional period; however, this requires women at risk to be adequately informed about the appropriate dosage and timing of supplement intake before planning another pregnancy. As birth defects surveillance programs are tasked with identifying and documenting NTD-affected pregnancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Eight publications surveyed 31–54 surveillance programs about methodologies, barriers, and programmatic activities. Two publications assessed NTD recurrence prevention activities among surveillance systems in 2005 and 2015, respectively (Collins et al, 2009; Flood et al, 2016), highlighting that few systems conducted activities to prevent NTD recurrence (e.g., 9 of 44 in 2015). Other publications identified that few surveillance programs (7 of 34) have interstate data exchange agreements with other state surveillance programs (Cassell et al, 2007), and only a slight majority (20 out of 38) of programs conduct geocoding of maternal address (Wang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Eight publications surveyed 31–54 surveillance programs about methodologies, barriers, and programmatic activities. Two publications assessed NTD recurrence prevention activities among surveillance systems in 2005 and 2015, respectively (Collins et al, 2009; Flood et al, 2016), highlighting that few systems conducted activities to prevent NTD recurrence (e.g., 9 of 44 in 2015). Other publications identified that few surveillance programs (7 of 34) have interstate data exchange agreements with other state surveillance programs (Cassell et al, 2007), and only a slight majority (20 out of 38) of programs conduct geocoding of maternal address (Wang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Flood et al suggested a list of recurrence prevention activities that can be undertaken with minimal staff requirements and may be applicable to hospital settings with limited resources toward recurrence prevention [ 10 ]. Some of these activities can be tailored to the Ethiopian context: (a) Educate mothers about recurrence risk and prevention and provide 5 mg/day folic acid supplement pills if they are planning a pregnancy in the near future; (b) Involve patient support groups to deliver educational messages about recurrence prevention; (c) Include health extension workers specifically targeting high-risk mothers in recurrence prevention programs; (d) Conduct outreach to high-risk women with information pamphlets and mobile phone messages on recurrence prevention; and (e) Reach high-risk mothers in a variety of clinical settings (e.g., obstetrics and gynecology, spina bifida clinic, primary healthcare centers, pediatric clinics).…”
Section: Discussionmentioning
confidence: 99%
“…One of the early studies, reported by Czeizel et al, highlighted a national program promoting folic acid to high-risk mothers, aiming at averting NTD recurrence risk in Hungary [ 9 ]. Currently, even within high-income countries such as the United States and Canada, very few states have birth defects surveillance programs that engage in recurrence prevention activities, and this is largely attributed to lack of allocated resources [ 10 ]. Two US-based studies showed the benefit of recurrence prevention programs in the US.…”
Section: Introductionmentioning
confidence: 99%